"Financialization" of public discourse: the case of AIG. Issue 4 (23rd September 2014) - Tanweer Ali, Dr; B. Avsar, Rojhat
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to demonstrate a particular shift in the language used in economic policy debates since the late 1970s. We call this phenomenon the "financialization of public discourse", which refers to the use of particular metaphors and linguistic styles that are friendly to the economic interest of the financial industry. Design/methodology/approach – We used a rhetorical analysis to discover and analyze the specific cases which exemplify what we call the financialization of public discourse. A case study, the USA Treasury's justification for its AIG policy, is used to strengthen the thesis of the paper. Findings – As the AIG case helps demonstrate, the language of finance limits the policy conversation and disguises the fact that the government's role in this case is not different than its overall collective risk management function. Research limitations/implications – We assume that framing of economic events helps shape public perceptions of the desirability of various policies. This prediction, although reasonable, should be supported with more direct evidence. Practical implications – This paper intends to articulate a vital risk management role that the government plays in the economy. Specifically, the government is strongly suited to spreading the consequences of aggregate risk over time and thereby insulating the individuals from drastic fluctuations in their welfare. Our approach could potentially inform an array of public policies. Originality/value – The rhetorical strategies that policy makers use to justify their policy positions and their consequences have been certainly under-researched, particularly in economics. This paper intends to fill this gap in the literature.